2013
DOI: 10.1021/jf403401v
|View full text |Cite
|
Sign up to set email alerts
|

Biological System Responses to Zearalenone Mycotoxin Exposure by Integrated Metabolomic Studies

Abstract: This study aims to investigate the effect of zearalenone supplementation on rat metabolism. Rats received biweekly intragastric administration of zearalenone mycotoxin (3 mg/kg body weight) for 2 weeks. Urine and plasma samples after zearalenone administration were analyzed by NMR-based metabolomics. Zearalenone exposure significantly elevated the plasma levels of glucose, lactate, N-acetyl glycoprotein, O-acetyl glycoprotein, and propionate but reduced the plasma levels of tyrosine, branched-chain amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 38 publications
8
41
0
Order By: Relevance
“…51,72 A previous report suggests that elevated levels of N-methylnicotinamide and decreased levels of nicotinate indicate increased oxidative stress response in vivo. 73 In our study, the elevation of urinary trigonelline and N-methylnicotinamide in mice administration with O-Tyr, and the elevation of urinary trigonelline in mice administration with Dityr, implied that mice can utilize an antioxidative vitamin B 3 cycle to decrease oxidative stress induced by O-Tyr and Dityr administration. The observation of an increased level of m-hydroxyphenylacetate, also implies antioxidative responses activated by O-Tyr and Dityr administration.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…51,72 A previous report suggests that elevated levels of N-methylnicotinamide and decreased levels of nicotinate indicate increased oxidative stress response in vivo. 73 In our study, the elevation of urinary trigonelline and N-methylnicotinamide in mice administration with O-Tyr, and the elevation of urinary trigonelline in mice administration with Dityr, implied that mice can utilize an antioxidative vitamin B 3 cycle to decrease oxidative stress induced by O-Tyr and Dityr administration. The observation of an increased level of m-hydroxyphenylacetate, also implies antioxidative responses activated by O-Tyr and Dityr administration.…”
Section: Discussionsupporting
confidence: 51%
“…A total of 47 metabolites in serum and 61 metabolites in urine were unambiguously assigned from the 1 H NMR spectra. Assignment of metabolites was made on the basis of comparisons with the published literature [44][45][46][47] and existing databases (such as the Human Metabolome Data Base). 48 In addition, for exact assignment purposes, ve two-dimensional (2D) NMR spectra including 1 H-1 H J-resolved spectroscopy (J-Res), 1 7A and 8A, respectively) showed there were no outliers within the dataset, and separations were absent in the metabolic serum and urine proles of mice from the control group, O-Tyr group, and DT group.…”
Section: Effects Of O-tyr and Dt Administration On The Antioxidant Enmentioning
confidence: 99%
“…In the present study, we found significant differences in the O-acetyl-glycoprotein, citrate, and creatinine concentrations among the three treatment groups. A previous study similarly showed that exposure to ZEA significantly elevated the plasma levels of glucose and O-acetyl glycoprotein (Liu et al, 2013). NMR has been used to identify the milk metabolites obtained from two dairy cow breeds (Danish and Jersey Holstein), and they found choline, creatinine, and citrate, which are also potential biomarkers (O'Sullivan et al, 2013;Pinotti et al, 2002).…”
Section: Analysis Of Plasma Metabolites and Metabolic Pathwaysmentioning
confidence: 94%
“…Our results also illustrate that mycotoxins affect glucose metabolites in the blood, thereby influencing glucose metabolism. Previous studies have shown that mycotoxin-contaminated feed can affect glucose metabolism, specifically by decreasing the activities of intestinal glucose transporters (Bertrand & Applegate, 2013;Liu et al, 2013;Zhang et al, 2011). Glucogenic amino acids are involved in the regulation of glucose metabolism (Xu et al, 2008).…”
Section: Analysis Of Plasma Metabolites and Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation